An early clinical comparative study on total knee arthroplasty with kinematic alignment using specific instruments versus mechanical alignment in varus knees - Wen, Liang; Wang, Zhiwei; Ma, Desi; Zhao, Xiaoxiong (Frontiers in Surgery, 2023)
Background: The kinematic alignment technique, as one of the alignment options for total knee arthroplasty, has attracted increasing attention from orthopedic surgeons and has been increasingly performed in the most populous countries in the world. The purpose of this study is to explore and compare the early clinical outcomes of total knee arthroplasty with KA using specific instruments versus mechanical alignment in our nation. Methods: A retrospective analysis was performed on patients who underwent unilateral total knee arthroplasty for knee osteoarthritis with varus deformity. Depending on the alignment method, patients were divided into a kinematically aligned total knee arthroplasty (KA-TKA) group and a mechanically aligned total knee arthroplasty (MA-TKA) group. The hip-knee-ankle (HKA) angle before and after surgery, the knee joint clinical score (KS-C), the knee joint functional score (KS-F) and the forgotten joint score (FJS) at three months and two years after surgery were recorded and statistically analyzed. Results: A total of 126 patients were enrolled, including 65 in the KA-TKA group and 61 in the MA-TKA group. The mean follow-up period was 30.8 months. The postoperative HKA angle was not significantly different at the 2-year follow-up between the two groups (P>0.05). The KS-C, KS-F and FJS scores in the KA-TKA group were higher than those in the MA-TKA group at 3 months after surgery, and the difference was statistically significant (P<0.05). At the 2-year follow-up, the KS-C, KS-F and FJS scores in the KA-TKA group were higher than those in the MA-TKA group, and the difference in the KS-C and FJS scores was statistically significant (P<0.05). Conclusion: Patients who underwent KA-TKA had a postoperative lower limb alignment similar to that of those who underwent MA-TKA. The clinical outcomes of KA-TKA were superior to those of MA-TKA in terms of clinical performance, knee function and subjective sensation up to 2 years after surgery.